2011
DOI: 10.1017/s0376892911000506
|View full text |Cite
|
Sign up to set email alerts
|

Applying the ecosystem services concept to poverty alleviation: the need to disaggregate human well-being

Abstract: SUMMARYThe concept of ecosystem services (ES), the benefits humans derive from ecosystems, is increasingly applied to environmental conservation, human wellbeing and poverty alleviation, and to inform the development of interventions. Payments for ecosystem services (PES) implicitly recognize the unequal distribution of the costs and benefits of maintaining ES, through monetary compensation from 'winners' to 'losers'. Some research into PES has examined how such schemes affect poverty, while other literature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
375
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(410 citation statements)
references
References 46 publications
5
375
0
10
Order By: Relevance
“…However, there has been insufficient attention to understanding well-being as co-created by people and ecosystems (Smith et al 2013), as well as incorporating the subjectivity of well-being in this context (Breslow et al 2016). It is notoriously difficult to assess human well-being in a way that captures fine-grained variations within or among groups of people in the same place (Raudsepp-Hearne et al 2010, Daw et al 2011, Russell et al 2012. Applying sense of place tools as an indicator of subjective well-being could contribute to meeting these challenges.…”
Section: Sense Of Place In Assessment Of Ecosystem Managementmentioning
confidence: 99%
“…However, there has been insufficient attention to understanding well-being as co-created by people and ecosystems (Smith et al 2013), as well as incorporating the subjectivity of well-being in this context (Breslow et al 2016). It is notoriously difficult to assess human well-being in a way that captures fine-grained variations within or among groups of people in the same place (Raudsepp-Hearne et al 2010, Daw et al 2011, Russell et al 2012. Applying sense of place tools as an indicator of subjective well-being could contribute to meeting these challenges.…”
Section: Sense Of Place In Assessment Of Ecosystem Managementmentioning
confidence: 99%
“…However, if the ES concept is to become a fully operational planning tool, it is necessary to move beyond this simplistic perception. Important trade-offs have been recognized between ecosystem management for extracting tangible products (such as food and fibre) versus maintaining intangible services (for example water regulation) (MEA 2005;Rodríguez et al 2006), but less attention has been given to the relationships between intangible ES (Daw et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, Kremen et al (2000) and McConnell (2002) proposed that the overall impacts of ecosystem services on human well-being cannot be determined by the research in one region or modeling through using shortterm data. Identically, Daw et al (2011) concluded that people benefited from ecosystem services constrained by the family size, education level, poverty, vulnerability, and social relations. These findings are also appropriate for hydrological ecosystem services.…”
Section: Effects Of Regional Hydrological Ecosystem Services On Humanmentioning
confidence: 99%